2017
DOI: 10.1039/c7cc00786h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced durability and activity of the perovskite electrocatalyst Pr0.5Ba0.5CoO3−δ by Ca doping for the oxygen evolution reaction at room temperature

Abstract: A promising Ca doping approach was reported to improve the durability and electrocatalytic OER activity of the perovskite PrBaCoO (PBC). Compared to the pristine PBC, the electrocatalytic activity of Ca-doped PrBaCaCoO perovskite was increased by ca. 90%. More importantly, its durability was significantly enhanced after doping with calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
1
38
0
5
Order By: Relevance
“…[66,68] Meanwhile,the electron redistribution is beneficial to charge transfer on the active sites from the electrode interface to the adsorbed reactants. [30,[69][70][71] In the case of the metal compound based material, doping by the non-noble atoms is one of the most common strategies. Xie et al reported the V-doped MoS 2 with amodified energy band structure ( Figure 4a).…”
Section: Metal-atom Dopantsmentioning
confidence: 96%
See 1 more Smart Citation
“…[66,68] Meanwhile,the electron redistribution is beneficial to charge transfer on the active sites from the electrode interface to the adsorbed reactants. [30,[69][70][71] In the case of the metal compound based material, doping by the non-noble atoms is one of the most common strategies. Xie et al reported the V-doped MoS 2 with amodified energy band structure ( Figure 4a).…”
Section: Metal-atom Dopantsmentioning
confidence: 96%
“…[70] Some similar results were also observed in the perovskite-type electrocatalysts. [30,71] Noble-metal atom is also used as ad opant to tune catalytic activity.B ao et al reported the Pt-doped MoS 2 with the significant h 10 value decreasing from 390 to 140 mV. [68] Therelated calculated results demonstrated that aseries of defect levels were induced near Fermi level of the in-plane Sa toms,w hich was quite analogical with the DOS of the active edge Sa toms in pure MoS 2 .A saresult, these reconstructed electronic configurations of the Pt-doped MoS 2 reduced the hydrogen adsorption energy from around 1.83 to approximately 0eVa nd consequently boosted the specific activity of HER.…”
Section: Metal-atom Dopantsmentioning
confidence: 99%
“…The overpotential can be lowered by electrocatalysts, such as IrO 2 and RuO 2 , which show high activity, but their scarcity, high cost and limitations in long‐term stability in alkaline solutions hamper their practical use . Designing inexpensive, earth‐abundant and efficient electrocatalysts with low overpotential, which are stable upon prolonged exposure to oxidizing conditions in alkaline solutions, has been a major challenge ,…”
Section: Figurementioning
confidence: 99%
“…[66,68] Zudem fçrdert die Elektronen-Umverteilung den Ladungstransfer an den aktiven Zentren von der Elektrodengrenzschichtz ud en adsorbierten Reaktanten. [30,[69][70][71] FürMaterialien, die auf einer Metallverbindung basieren, ist die Dotierung mit unedlen Atomen eine der häufigsten Strategien. Xie et al berichteten über Va nadium-dotiertes MoS 2 mit einer modifizierten Energiebandstruktur (Abbildung 4a).…”
Section: Metallatom-dotandenunclassified
“…[70] Einige ähnliche Ergebnisse wurden auch fürP erowskit-Typ-Elektrokatalysatoren erhalten. [30,71] Edelmetallatome fanden ebenfalls Verwendung als Dotanden, um die katalytische Aktivitätz u steigern. Bao et al berichteten über Pt-dotiertes MoS 2 ,f ür das der signifikante h 10 -Wert von 390 auf 140 mV abfiel.…”
Section: Angewandte Chemieunclassified